2003
DOI: 10.1016/s0954-6111(03)00129-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 levels in the pathophysiology of chronic obstructive pulmonary disease and bronchial asthma

Abstract: According to our results: (1) ET-1 levels were significantly higher in "desaturators" COPD patients than in "non-desaturators" COPD and in asthmatics; (2) ET-1 levels were significantly higher during the night than during the day in "desaturators" COPD patients; (3) the degree of desaturation correlated negatively with the ET-1 levels in "desaturators" COPD patients, both during daytime and nighttime. These findings are consistent with the hypothesis that ET-1 is implicated in the pathophysiology of asthma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
3
31
1
1
Order By: Relevance
“…Levels of ET-1 were increased in CS and CH groups, consistent with the increased levels observed in smokers and COPD patients [29,30]. However, no differences in ET-1 levels were observed in CSCH animals, suggesting that the synergistic effect on Ppa does not appear to be mediated by ET-1 in plasma.…”
Section: Discussionsupporting
confidence: 80%
“…Levels of ET-1 were increased in CS and CH groups, consistent with the increased levels observed in smokers and COPD patients [29,30]. However, no differences in ET-1 levels were observed in CSCH animals, suggesting that the synergistic effect on Ppa does not appear to be mediated by ET-1 in plasma.…”
Section: Discussionsupporting
confidence: 80%
“…Among a wide range of phlogogenic molecules affecting the development of systemic inflammation in COPD one should also mention the vasoactive mediator ET-1 [30]. The results of this study showed an increase in the level of this peptide in all COPD patients compared to the reference group.…”
supporting
confidence: 48%
“…Plasma ET-1 concentrations are also elevated in COPD patients, particularly in patients who develop nocturnal hypoxemia during the night (Trakada et al, 2001;Spiropoulos et al, 2003) and in patients with hypoxemia (Faller et al, 1998), but it is not correlated with secondary pulmonary hypertension (Bacakoglu et al, 2003). This may reflect the release of ET-1 by hypoxemia, suggesting that the release of ET-1 may contribute to pulmonary vasoconstriction and pulmonary hypertension in COPD patients.…”
Section: Formationmentioning
confidence: 99%